Aves exóticas en el AICA Humedales de Alvarado, Veracruz, México/ Exotic birds in the IBA Humedales de Alvarado, Veracruz, Mexico - Ramírez-Bastida, Patricia; Ruiz-Rodríguez, Amira; Navarro Sigüenza, Adolfo G.; Vargas-Gómez, Mishael; García-Valencia, Uriel Daniel (Instituto de Ecología, A.C., 2015)
We report records of Eurasian Collared-Dove (Streptopelia decaocto), Monk Parakeet (Myiopsitta monachus), and Orange-fronted Parakeet (Eupsittula canicularis), in the estuaries and floodplains of the Important Bird Area ‘Humedales de Alvarado’, Veracruz, from 2011 to 2014. Both exotic Parakeets were observed in mixed flocks with native Olive-throated Parakeet (Eupsittula nana). These species can out compete for resources with native birds andneed to be monitored. Both S. decaocto and M. monachus are successfulinvaders in many urban areas of Mexico.